1974
DOI: 10.1037/h0037334
|View full text |Cite
|
Sign up to set email alerts
|

Predicting absenteeism and turnover: A field comparison of Fishbein's model and traditional job attitude measures.

Abstract: The present investigation studied the lab-to-field generalizability of Fishbein's attitude-behavior model and examined the relative efficacy of the Fishbein model and traditional job attitude measures as predictors of absenteeism and turnover. Predictor data were collected from 108 nursing home employees immediately preceding the two-month time period of interest. Criterion data were obtained at the end of the two-month period. Fishbein's model received some field support, particularly with respect to predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
5

Year Published

1980
1980
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 8 publications
6
71
0
5
Order By: Relevance
“…4 and 5). The strength of this relationship is weak however, as found in studies outside nursing (Farrell and Stamm, 1988;Hackett and Guion, 1985 ;Scott and Taylor, 1985 ;Newman, 1974). All these studies confirm Locke's (1976) observation that the magnitude of the relationship between job satisfaction and absence seldom surpasses -0.4 and is typically, as in the present study, much lower.…”
Section: Discussionsupporting
confidence: 86%
“…4 and 5). The strength of this relationship is weak however, as found in studies outside nursing (Farrell and Stamm, 1988;Hackett and Guion, 1985 ;Scott and Taylor, 1985 ;Newman, 1974). All these studies confirm Locke's (1976) observation that the magnitude of the relationship between job satisfaction and absence seldom surpasses -0.4 and is typically, as in the present study, much lower.…”
Section: Discussionsupporting
confidence: 86%
“…This is in light of other researchers (Fishbein 1967;Newman 1974;Mathieu and Zajac 1990) who assert that employees' attitudes mediate the relationship between beliefs/perceptions and behavioral intentions.…”
Section: Introductionsupporting
confidence: 65%
“…The findings in this area, however, are not entirely consistent. Several studies found a positive relationship between the two variables (Kraut, 1970;Newman, 1974;Alley and Gould, 1975;Porter et al, 1976;etc.). In contrast, C. A. O'Reilley and K. H. Roberts (1978), R. Hampton et al, 1986) reported no linkages between organizational commitment and leadership styles, whereas J. G. Hunt and V.K.C.…”
Section: Relationship Between Organizational Commitment and Leadershimentioning
confidence: 99%